Role of anxiety in willingness to communicate in the Jordanian EFL context - Al-Saidat, Emad; Dipima Buragohain,; Amer, Faten (Penerbit Universiti Kebangsaan Malaysia, 2023)
Anxiety is understood as being worried, an emotional reaction that accompanies one’s learning. In the foreign language context, it may hinder the language learning experience and lead to communication apprehension. This study investigates the role of anxiety in the willingness to communicate across Jordanian EFL eighth-grade students at a private school in Amman. Direct observations and interviews were conducted across twenty students and two teachers. The analysis of data obtained from observations showed that the majority of students were reluctant to participate in English classrooms, as only an average of 10% showed their desire to participate in all the observational categories. Firstly, the interview data showed that anxiety affected students’ willingness to communicate inside classrooms. Secondly, students’ level of anxiety was found to be increased by several factors such as fear of making mistakes, fear of being criticised by other people inside the classroom, including the teacher, and fear of negative teacher evaluation. Thirdly, the results also showed that some of the reasons that led to anxiety stemmed from cultural beliefs deeply rooted in the students concerning being active participants or speaking in front of other people. Finally, the study provides some recommendations for teachers in order to create an anxiety-free learning atmosphere in classrooms to reduce students’ speaking anxiety.